Condicionamento de sementes florestais visando a recuperação de áreas degradadas pela exploração petrolífera na Amazônia brasileira - Calvi, Geângelo Petene (Instituto Nacional de Pesquisas da Amazônia - INPA, 2008)
This thesis is divided into two parts. In the first part, three degraded areas by oil exploration in Coari (Amazonas State) at the “Base Operacional Geólogo Pedro de Moura” (BOGPM), were selected to evaluate their revegetation after (a) installing perches, (b) spreading out additional top-soil or (c) mounting cohorts of dead branches. The preliminary results indicated a significant increase of seedling density with additional top-soil, while the other techniques showed no alteration compared to the control in the first four months after installation of the experiment. With the aim to accelerate the recuperation of these areas by direct sowing, the second part of this thesis was dedicated to improve seed priming of two tree species from non flooded tropical forest of the Amazon. Parkia multijuga Benth seeds were imbibed to different hydration levels at 15 ºC before subsequent slow drying at 25 ± 1 ºC and 64 ±2 % UR comparing hydropriming by submersion in aerated water with matriconditioning between moistened cotton clothes. Only matriconditioning increase significantly germination rate and speed. However, because the imprecision in the inference of moisture content on seeds after pre-established imbibition time and difficult seed handling using moistened cotton clothes, was necessary the technique improvement. Subsequently matriconditioning in plastic bags with moistened vermiculite (1 g vermiculite : 2,5 g water) was tested at 15 ºC with seeds of P. multijuga and Jacaranda copaia (Aubl.) D. Don. This technique improved significantly the germination percentage and speed of low quality seeds of both species. Imbibition for 4 hours increased germination performance of J. copaia seeds from 24 % (Mean Germination Time - MGT 30,0 d) to 48 % (MGT 28,4 d); and imbibition for 2 days of P. multijuga seeds from a 63 % (MGT 23,2 d) to 82 % (MGT 20,7 d). Although other seed lots should be tested before recommending a protocol, the matriconditioning with moistened vermiculite increased germination performance of seeds of two species tested.
Keywords: Recuperação de áreas degradadas; Semeadura direta; Técnica de nucleação